Implementasi Program Santunan Kematian Berbasis Online dalam Mendukung Denpasar Smart City - Hartajaya Devi GN, Komang Ayu; Sastra Wijaya, Komang Adi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2020)
ABSTRACT The Online-Based Death Compensation Program is an innovation that aims to increase the transparency of the death compensations program and maximizing process to improve services to the people of Denpasar City including veterans. This program is one of the best programs in organizing Denpasar Smart City. This study uses descriptive qualitative methods with data collection techniques such as observations, interviews, and documentations. The results of the study are based on an analysis with three implementation indicators according to Charles O. Jones showing that the program still needs to be optimized because there are still problems with several indicators such as: the need to consider the number of death compensation operators, not yet maximizing socialization to the community especially in terms of requirements, the process of disbursing funds which often exceeds the time limit specified, and the amount of compensation funds expected to increase especially given to the community. Keywords: Implementation, Online Based Death Compensation Program, Denpasar Smart City.